Proceedings of the 9th European Conference on Interactive TV and Video 2011
DOI: 10.1145/2000119.2000165
|View full text |Cite
|
Sign up to set email alerts
|

User experience of elderly people with digital television

Abstract: The paper introduces a qualitative investigation to explore and analyse user experience of elderly people (age range from 70 to 79) with digital television and, more in general, with future services made available by broadband ICTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…In the following, the main results are summarized for each UTAUT construct. The most significant quotations stated by the older adults in the study can be found in [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the following, the main results are summarized for each UTAUT construct. The most significant quotations stated by the older adults in the study can be found in [26].…”
Section: Resultsmentioning
confidence: 99%
“…User experience during transition from analogue to digital terrestrial television was presented in [26], focusing on older adults (age range from 70 to 79).…”
Section: Field Study 3: Older Adults' Acceptance Of Digital Televisionmentioning
confidence: 99%
“…From the perspective of older people, future services and applications of ICT should support the development of social relations through communication, as they see the main benefits of technology as connecting to family and friends (Ferreira et al, 2014), lamenting how activities such as watching TV used to be a group activity (Papa et al, 2011). Looking at human connectivity beyond family and friends and through activities, Baez and colleagues (2019) pointed out the significant role of mediators or facilitators in connecting older people through ICT in their findings that the use of peer assistants was effective for older people in adapting to technology.…”
Section: Digital Delivery Of Social Connectivity Toward Social Inclusionmentioning
confidence: 99%
“…Other barriers were the cost of digital TV systems and a perceived lack of human support. Papa [7] conducted focus groups to explore and analyze the user experience of older people with digital TV and, in general, with future services enabled by broadband ICTs. The results show the influence that aspects such as the technological equipment available at home, the attitude towards digital technology and lifestyles can have on older people's interaction with digital TV.…”
Section: Older People and Itvmentioning
confidence: 99%